THE WAY FORWARD FOR BUSINESS INCUBATION PROCESS IN ICT INCUBATORS IN MALAYSIA - Abdul Khalid, Fararishah; Gilbert, David; Huq, Afreen (2014)
The development of ICT SMEs has been the top priority for Malaysia, in trying to achieve its aspirations to become a fully developed nation by the year 2020. The government has launched several initiatives to expedite the launch and growth of ICT SMEs including the establishing science parks, technology parks, and business incubators. This paper examines the critical components that are essential in a business incubation ecosystem. Six ICT incubator managers in Malaysia were interviewed and findings from the interviews revealed that although process of business incubation is evident in all incubators, there is a lack in consistency and implementation. This paper provides a managerial perspective of business incubation process in ICT incubators and the way forward for these incubators to become world-class ICT incubators.